Evaluation of the Capacity of Main Sewage Pipeline in The Center of Karbala City Under the Impact of The Rainfall Derived Infiltration and Inflow (RDII) - Ali N. Ghulam; Basim K. Nile; Jabbar H. Al-Baidhani (International Journal of Computational and Experimental Science and Engineering, 2025)
The sanitary sewer network is one of the most important pillars of infrastructure and is affected by many variables today. The aging of the network, increasing urbanization, climate change and high consumption all lead to a continuous challenge to the operation and efficiency of the network. One of the most important problems facing sewage networks is the Rainfall Derived Infiltration and Inflow (RDII), which is one of the main causes of sewer overflows with the negative repercussions it causes to health and the environment. The current research focused on evaluating the effect of the RDII on the capacity of the main sewage pipe in the center of Karbala city in Iraq, that receives millions of pilgrims annually during a short period of time during which the sewage network is under high consumption pressure. recorded data of discharge and rainfall were analyzed using the SSOAP and PCSWMM software. The analysis results showed that high levels of RDII entered the network during a rainfall depth of 25 mm, which led to an increase in maximum hourly discharge to 86%, an increase in total daily discharge to 21.5% and the capacity of the main pipe in the critical area reached 91%.